Administrative law in action : immigration administration - Thomas, Robert (London [England] : Hart Publishing, 2022)
"This book investigates and analyses how administrative law works in practice through a detailed case-study and evaluation of one of the UK's largest and most important administrative agencies, the immigration department. In doing so, the book broadens the conversation of administrative law beyond the courts to include how administrative agencies themselves make, apply, and enforce the law. Blending theoretical and empirical administrative-legal analysis, the book demonstrates why we need to pay closer attention to what government agencies actually do, how they do it, how they are organised, and held to account. Taking a contextual approach, the book provides a detailed analysis of how the immigration department performs its core functions of making policy and law, taking mass casework decisions, and enforcing immigration law. The book considers major recent episodes of immigration administration including the development of the hostile environment policy and the treatment of the Windrush generation. By examining a diverse range of material, the book presents a model of administrative law based upon the organisational competence and capacity of administration and its institutional design. Alongside diagnosing the immigration department's failings, the book advances positive proposals for its reform."--
1. Law and administration -- 2. The Development and Operation of the Immigration Agency -- 3. Administrative Policy-making: A Case Study of the Hostile Environment Policy -- 4. Administrative Rule-Making -- 5. Casework decision-making -- 6. Immigration Enforcement -- 7. Legal Challenges and Means of Redress Against Immigration Decisions -- 8. Substantive Judicial Review 9 Bureaucratic Oppression -- 10. Conclusion -- Bibliography -- Index.
Includes bibliographical references and index.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Emigration and immigration law -- Great Britain; Great Britain -- Emigration and immigration -- Government policy; Electronic books